Protective protein/cathepsin A rescues N-glycosylation defects in neuraminidase-1 - Wang, Dongning; Zaitsev, Slava; Taylor, Garry; d'Azzo, Alessandra; Bonten, Erik (Biochimica et biophysica acta, 2009)
Neuraminidase-1 (NEU1) catabolizes the hydrolysis of sialic acids from sialo-glycoconjugates. NEU1 depends on its interaction with the protective protein/cathepsin A (PPCA) for lysosomal compartmentalization and catalytic activation. Murine NEU1 contains 4 N-glycosylation sites, 3 of which are conserved in the human enzyme. The expression of NEU1 gives rise to differentially glycosylated proteins. We generated single-point mutations in mouse NEU1 at each of the 4 N-glycosylation sites. Mutant enzymes were expressed in NEU1-deficient cells in the presence and absence of PPCA. All 4 N-glycosylation variants were targeted to the lysosomal/endosomal compartment. All N-glycans, with the exception of the most C-terminal glycan, were important for maintaining stability or catalytic activity. The loss of catalytic activity caused by the deletion of the second N-glycan was rescued by increasing PPCA expression. Similar results were obtained with a human NEU1 N-glycosylation mutant identified in a sialidosis patient. The N-terminal N-glycan of NEU1 is indispensable for its function, whereas the C-terminal N-glycan appears to be non-essential. The omission of the second N-glycan can be compensated for by upregulating the expression of PPCA. These findings could be relevant for the design of target therapies for patients carrying specific NEU1 mutations.